Comparison of the Efficacy of Atopalm® Multi-Lamellar Emulsion Cream and Physiogel® Intensive Cream in Improving Epidermal Permeability Barrier in Sensitive Skin. Issue 1 (March 2016) - Jeong, Sekyoo; Lee, Sin; Park, Byeong; Wu, Yan; Man, George; Man, Mao-Qiang
Abstract Introduction The management of sensitive skin, which affects over 60% of the general population, has been a long-standing challenge for both patients and clinicians. Because defective epidermal permeability barrier is one of the clinical features of sensitive skin, barrier-enhancing products could be an optimal regimen for sensitive skin. In the present study, we evaluated the efficacy and safety of two barrier-enhancing products, i.e., Atopalm® Multi-Lamellar Emulsion (MLE) Cream and Physiogel® Intensive Cream for sensitive skin. Methods 60 patients with sensitive skin, aged 22–40 years old, were randomly assigned to one group treated with Atopalm MLE Cream, and another group treated with Physiogel Intensive Cream twice daily for 4 weeks. Lactic acid stinging test scores (LASTS), stratum hydration (SC) and transepidermal water loss (TEWL) were assessed before, 2 and 4 weeks after the treatment. Results Atopalm MLE Cream significantly lowered TEWL after 2 and 4 weeks of treatment (p < 0.01). In contrast, Physiogel Intensive Cream significantly increased TEWL after 2 weeks of treatment (p < 0.05) while TEWL significantly decreased after 4-week treatments. Moreover, both Atopalm MLE Cream and Physiogel Intensive Cream significantly increased SC hydration, and improved LASTS after 4 weeks of treatment. Conclusion Both barrier-enhancing products are effective and safe for improving epidermal functions, including permeability barrier, SC hydration and LASTS, in sensitive skin. These products could be a valuable alternative for management of sensitive skin. Funding Veterans Affairs Medical Center, San Francisco, California, USA, and NeoPharm Co., Ltd., Daejeon, Korea.